Bone Lining Cells Could Be Sources of Bone Marrow Adipocytes - Lee, Ji Yeon; Yang, Jae-Yeon; Kim, Sang Wan (Frontiers in Endocrinology, 2021)
Background: Recently, lineage-tracing studies demonstrated that parathyroid hormone and anti-sclerostin antibody (Scl-Ab) can convert bone lining cells (BLCs) into active osteoblasts. However, BLCs might also be differentiated into other lineages. Here we investigated whether BLCs could differentiate into bone marrow adipocytes (BMAds) and whether Scl-Ab could suppress this process. Methods: Dmp1-CreERt2:mTmG mice were injected with 0.5 mg of 4-hydroxytamoxifen once weekly from postnatal week 4 to week 8. The mice were treated with either vehicle or rosiglitazone for 8 weeks (weeks 12–20). Moreover, they were administered either vehicle or Scl-Ab (50 mg/kg) twice weekly for 4 weeks (weeks 16–20, N = 4–6/group). We chased the GFP+ cells from the endosteal surface to the bone marrow (BM) of the femur. Using immunohistochemical staining, the numbers of perilipin+ or GFP+/perilipin double+ cells in the BM were quantified. In addition, serum N-terminal propeptide of type I procollagen (P1NP) levels were measured at each time point, and bone mass was analyzed at 20 weeks using micro-computed tomography. Results: Scl-Ab administration significantly reversed the decreases in bone parameters induced by rosiglitazone. Plump GFP+ cells, presumably active osteoblasts, and extremely flat GFP+ cells, presumably BLCs, were present on the endosteal surface of the femur at 8 and 12 weeks, respectively, in line with prior findings. When we chased the GFP+ cells, rosiglitazone significantly increased the number of GFP/perilipin double+ BMAds compared to the effects of the vehicle (P < 0.001), and overlapping Scl-Ab administration decreased the number of GFP/perilipin double + BMAd compared to rosiglitazone alone (P < 0.001). In addition, we found that osteoblast lineage cells such as BLCs might express PPAR on immunohistochemical staining. When rosiglitazone was administered to Rip-Cre:mTmG mice, GFP+ cells were not present on the endosteal surface or in the BM of the femur; however, they were present in the pancreas. Conclusion: BLCs could be sources of BMAds, and rosiglitazone could stimulate the differentiation of osteoblast lineage cells into BMAds. Suppression of the differentiation of osteoblast lineage cells into BMAds might contribute to anabolic effects resulting from the pharmacologic inhibition of sclerostin.